Money on the move : the revolution in international finance since 1980 - Solomon, Robert (Princeton, N.J. : Princeton University Press, 1999)
In this book the author presents the history of monetary order between 1945 and 1981 and other aspects of this revolution in international finance. He talked about the rise and decline of foreign exchange value of the U.S. dollar, the debt crisis of developing countries, the shift from central planning to market economies and the move to a single European currency.
Includes bibliographical references (p. 177-199) and index.
nmn, 22/07/16
Loan
Keywords: International finance; Money; International trade